If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -2 + 3x + -14 + 18 + -5x = 2x + 3x + -10 + 11 Reorder the terms: -2 + -14 + 18 + x + 3x + -5x = 2x + 3x + -10 + 11 Combine like terms: -2 + -14 = -16 -16 + 18 + x + 3x + -5x = 2x + 3x + -10 + 11 Combine like terms: -16 + 18 = 2 2 + x + 3x + -5x = 2x + 3x + -10 + 11 Combine like terms: x + 3x = 4x 2 + 4x + -5x = 2x + 3x + -10 + 11 Combine like terms: 4x + -5x = -1x 2 + -1x = 2x + 3x + -10 + 11 Reorder the terms: 2 + -1x = -10 + 11 + 2x + 3x Combine like terms: -10 + 11 = 1 2 + -1x = 1 + 2x + 3x Combine like terms: 2x + 3x = 5x 2 + -1x = 1 + 5x Solving 2 + -1x = 1 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 2 + -1x + -5x = 1 + 5x + -5x Combine like terms: -1x + -5x = -6x 2 + -6x = 1 + 5x + -5x Combine like terms: 5x + -5x = 0 2 + -6x = 1 + 0 2 + -6x = 1 Add '-2' to each side of the equation. 2 + -2 + -6x = 1 + -2 Combine like terms: 2 + -2 = 0 0 + -6x = 1 + -2 -6x = 1 + -2 Combine like terms: 1 + -2 = -1 -6x = -1 Divide each side by '-6'. x = 0.1666666667 Simplifying x = 0.1666666667
| v/7=11.2 | | 15-4x=27x | | y-(-3)=-(9/2)(x-1) | | 11-3x=14x | | (x+6-5y)=(x-4+8) | | -24=-4/3y | | -(x+6-5y)=(x-4+8) | | 2(2x+3)3(5x+4)= | | (0.25*X)+X=3665.00 | | 6-2z=18-3z | | -3/4w=15 | | f*4+5=11 | | .25x=1567.50 | | (a+3)(a+3)=0 | | 3cos^2(x)-5cos(x)=2 | | -u/u^2 | | x-7(2x-3)=2(5x-2)-3(4x+9) | | (36y^2)-5=y-18y^2 | | -2+3(x-4)=3x-9(x-3)-1 | | 7(x-8)+9=5(x-7) | | 4x-2y=800 | | 5x+3-1*2=54 | | 7(x+6)+x=4(4x+4)+6 | | 2a+7=25+8 | | .417/.875 | | 3x-2(3x-2)=6-(3x-8)+9x | | 7(x-3)+x=2(x+5)+2 | | X^2+x-2=x^3 | | 5/12/7/8 | | (-4+7i)(1+i)= | | 4(2x+5)-(8x+5)=15 | | (3x^4)/(6)=x^6/30 |